(untitled) (Fiep Bulletin - online, 2016)
The research aimed to identify the burden on caregivers who provide care for bedridden elderly and describe the profile of the same in the catchment area of the Health Unit School in the city of Cascavel, PR. The sample was consisted of ten caregivers, who provided care for bedridden elderly and the data collection was based on the Zarit Scale, consisting of twenty-two (22) locked items, encompassing the assessment of perceived impact on physical and emotional health, social activities and financial condition. The scale was applied to the caregivers in the second half of April 2014. According to the results found in the survey, the age group of them ranged from 36 to 82 years with a mean of 63.3 years, predominantly female, 40% of these caregivers were married, 40% widows 20% single women and 70% do not have eight years of study. It was found that 90% of care are exercised by the family and only 10% is formal caregiver and receive 3-4 times the minimum wage. In the evaluation of the degree of overload of the group of caregivers (N = 10) 40% consider little or no overhead, 10% mild to moderate load and 50% load with moderate to severe. Therefore, health teams that deal with older people should turn his gaze not only for the provision of specialized services to those people, but also for the care of family caregivers.